Assessment of responsible innovation methods and practices - Yaghmaei, Emad; Poel, Ibo van de, 1966- (Routledge, Taylor & Francis Group, 2021)
"Responsible Innovation encourages innovators to work together with stakeholders during the research and innovation process, to better align the outcomes of innovation with the values, needs and expectations of society. Assessing the benefits and costs of Responsible Innovation is crucial for furthering the responsible conduct of science, technology and innovation. However, there is until now only limited academic work on Responsible Innovation assessment. This book fills this lacuna. Assessment of Responsible Innovation: Methods and Practices presents tools for measuring, monitoring, and reporting upon the Responsible Innovation process and the social, environmental, scientific, and economic impacts of innovations. These tools help innovators to mitigate risk and to strengthen their strategic planning. This book aligns assessment tools and practices with the UN Sustainable Development Goals (SDGs). The prospects as well as the limitations of various Responsible Innovation assessment approaches and tools are discussed, as well as their applicability in various industry contexts. The book brings together leading scholars in the field to present the most comprehensive review of Responsible Innovation tools. It articulates the importance of assessment and value creation, the different metrics and monitoring systems that can be deployed and the reporting mechanisms, including the importance of effective communication"--